0690 An Evaluation Of Genioglossus Strengthening On Obstructive Sleep Apnea Treatment Outcomes. (27th May 2020) - Maghsoudipour, M; Bosompra, N; Jen, R; Li, Y; Moore, S; DeYoung, P; Fine, J; Edwards, B; Gilbertson, D; Owens, R; Morgan, T; Malhotra, A
Abstract: Introduction: Obstructive sleep apnea (OSA) is characterized by repetitive episodes of pharyngeal collapse. The genioglossus is a major upper airway dilator muscle thought to be important in OSA pathogenesis. Upper airway (UA) muscle training has reported benefits in some OSA patients. Our goal was to assess the effect of upper airway muscle training on OSA outcomes. Methods: Sixty five patients with OSA (AHI>10/h) were divided in three subgroups: 1) Treated with auto-CPAP (n=21), 2) Previously failed or refused CPAP therapy (no treatment), (n=24), 3) Currently treated with an oral appliance who still have residual OSA (AHI>10/h), (n=20). All subjects were given a custom-made tongue strengthening device. Within each group we conducted a prospective, randomized, controlled study examining the effect of upper airway muscle training. In each subgroup, subjects were randomized to UA muscle training (volitional protrusion against resistance) or sham group (negligible resistance), with 1:1 ratio over 6 weeks of treatment (twice daily for 20 min/session). In the baseline and the final visit, subjects completed home sleep testing, questionnaires (ESS, PSQI), acoustic pharynogometry, Iowa Oral Performance Instrument (IOPI), and Psychomotor Vigilance Test (PVT). Results: Results remain blinded; 33 patients received treatment Y and 32 patients received treatment Z. To date, we have not observed a main effect of treatment group on several measures of OSA severity. Some changes in subjective measures over time were observed but difficult to interpret until unblinding occurs. Conclusion: Treatment of OSA using upper airway muscle training exercises requires further study. Whether muscle training is a viable approach for a definable subset of OSA patients remains unclear. Support: R01HL085188-05A1 (U.S. NIH Grant/Contract)